Pengaruh Konsep Diri, Masa Kerja dan Latar Belakang Pendidikan terhadap Motivasi Kerja Kepala RA - Ida Windi Wahyuni; Alucyana Alucyana; Dian Tri Utami (Universitas Al-Hikmah Indonesia, 2020)
This study focuses on self-concept, years of service, and educational background that affect the work motivation of the head of RA Pekanbaru City. The hypothesis proposed is that there is an influence between self-concept, years of service, and educational background on the work motivation of the Head of The Raudhatul Athfal City of Pekanbaru. The subjects of this study were 27 RA Heads of Pekanbaru City. The data analysis technique is correlation analysis in the SPSS for Windows program. The results of the study between self-concept, years of service and educational background influence the work motivation of RA heads, expressed in the results of the study with an R Square value of 28% (0.282), higher than the value of σ = 5% and an F value of 6.913 above the value 10% showing no symptoms of multicollinearity. This study states that self-concept, years of service, and educational background have a significant effect on the work motivation of the head of the RA City of Pekanbaru. The effect of self-concept, years of service, and educational background on work motivation show a significance value (Sig.) Of 0.010 with a value of σ (significant degree) 0.05, meaning 0.01 <0.05; meaning is that there is a significant influence between the influence of self-concept, years of service and educational background on the work motivation of RA Kota Pekanbaru head